The value of eosinophilic cationic protein in atopic dermatitis - Sergiy; Nadia; Ehab; Yulia; Vitaliy (Journal of Pakistan Association of Dermatologists, 2022)
Objective Till date, the search for diagnostic markers of atopic dermatitis (AD) is still active. Such investigations will assess not only the allergic inflammation, but also help controlling the severity of the disease. Â Method To analyze diagnostic significance of eosinophilic cationic protein in AD patients, a number of 24 patients with AD and 10 practically healthy persons were examined. The patients in the main study group were distributed by age: 18-40 years (12 persons) and over 40 years (12 persons). All AD patients were tested for allergic inflammation makers. Statistical processing of the obtained results was carried out by the method of variational statistics using the Statistica 10. Â Results With ageing, there was a tendency to a decreased number of AD extrinsic (high levels of IgE), instead the number of people with AD intrinsic increased (low levels of IgE) (OR = 2.92; 95% CI 1.83-4.65; p <0.001). In addition, both the forms of AD and the total serum IgE level were dependent on the age of the patients (OR = 5.72, 95% CI [2.52â€“13.94]; p <0.001). Simultaneously, when the severity of AD increased, ECP levels were increased significantly (OR = 4.26, 95% CI [2.01â€“9.05)]. Â Conclusion It is efficient to determine the level of ECP in AD, as an indicator for allergic inflammation. The levels of ECP increased with the severity of the disease. The level of ECP did not depend on the age of the patient and the form of AD. Â